(untitled) (London Journal of Research In Science: Natural and Formal, 2026)
This paper is based on the idea that all life was developed through evolution. I examine how evolution could have generated a subconscious mind. I then address several additional topics, such as the sense of responsibility, as well as systems like capitalism and communism.